2002
DOI: 10.1103/physreve.66.026108
|View full text |Cite
|
Sign up to set email alerts
|

Finite size scaling in the two-dimensionalXYmodel and generalized universality

Abstract: In recent works [S. T. Bramwell, P. C. W. Holdsworth, and J.-F. Pinton, Nature (London) 396, 552 (1998); S. T. Bramwell et al., Phys. Rev. Lett. 84, 3744 (2000)], a generalized universality has been proposed, linking phenomena as dissimilar as two-dimensional (2D) magnetism and turbulence. To test these ideas, we performed Monte Carlo simulations of the 2D XY model. We found that the shape of the probability distribution function for the magnetization M is non-Gaussian and independent of the system size-in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…From a visual point of view the distribution looks very similar across the critical, vortex free, region. The temperature dependence established here is weaker than, but of the same magnitude as, that claimed by Palma et al, for the full XY model [33]. More work is needed to fully understand this difference.…”
Section: Resultsmentioning
confidence: 44%
“…From a visual point of view the distribution looks very similar across the critical, vortex free, region. The temperature dependence established here is weaker than, but of the same magnitude as, that claimed by Palma et al, for the full XY model [33]. More work is needed to fully understand this difference.…”
Section: Resultsmentioning
confidence: 44%
“…Nevertheless, more recently [10] a numerical study of the full 2D XY-model was performed, and the results suggested a small but systematic dependence of the PDF on the system temperature. This numerical analysis was performed by using high precision Monte Carlo simulations, which amounts to control the statistical independence of the configurations used to compute thermodynamical averages, as this system is affected by the well known critical slowing down effect.…”
mentioning
confidence: 99%
“…The former have been discussed in detail in Ref. [5,21]; at fixed temperature, they give small deviations from the universal curve for small system size, L. These are finite size corrections to the thermodynamic limit function and disappear with relatively modest increase in the system size.…”
mentioning
confidence: 99%